C-Reactive protein / prealbumin coefficient, as a new marker in diagnosis and monitoring of the treatment efficacy in patients with malignant obstructive jaundice, complicated by ascending cholangitis - Levchenko, Liudmyla; Dronov , Olexii (The Ukrainian Scientific Medical Youth Journal, 2022)
preoperative ascending cholangitis is one of the main factors of unsatisfactory treatment outcomes and prognosis in patients with malignant obstructive jaundice. The aim of our study was to evaluate the diagnostic value of CRP /PA coefficient in preoperative ascending cholangitis diagnosis, the effectiveness of preoperative preparation and the possibility of infectious complications, which will improve the treatment quality and prognosis of this cohort of patients. The end points of the study were: to determine the reference rate of the СRP/PA coefficient; to evaluate the coefficient value for cholangitis and its severity at the stages of treatment; assess its importance in detecting postoperative infectious complications. A one-center prospective study of the treatment results of 84 patients who underwent biliary decompression in the preoperative period was conducted. All patients were diagnosed with preoperative ascending cholangitis according to the Tokyo Guidelines, 2018 criteria - I grade - in 48 (57.1%) patients, II grade - in 36 (42.9%) patients. It was determined that the median СRP/PA in healthy patients was 0.01 (0.01-0.02) of the main surgical intervention was significantly higher - 0.21 (0.13-0.45) and 0.02 (0.01-0.03) than in healthy individuals - 0.01 (0.01-0.02) ); p <0.001 and p = 0.004, respectively, we found a statistically difference between the medians of the СRP/PA level in patients with mild to moderate preoperative ascending cholangitis (p <0.001), which is confirmed by the correlation between the severity grade of cholangitis and СRP/PA value (r = 0,381, p <0,001). It was found that the preoperative biliary drainage increases the probability of reducing the СRP/PA level by 18% (R = 0,42, R2 = 0,18, p <0,001), increase СRP/PA level before drainage is associated with the presence of mixed biliary tract infection in 25% cases (R2 (Nagelkerke) = 0.25, p = 0.002) and it's also associated with an increased the rate of infectious complications from postoperative wound by 18 .9% (R2 (Nagelkerke) = 0.189, p = 0.005). CRP/PA coefficient may indicate preoperative ascending cholangitis diagnosis and its severity ​​in patients with malignant obstructive jaundice. Increase СRP/PA level before preoperative biliary drainage is associated with the presence of mixed biliary tract flora and possibility of infectious complications. The dynamics of the coefficient value can show the efficacy of preoperative preparation after biliary decompression and predict correct time for surgery, which improves the treatment prognosis in postoperative period.